Price stability and monetary policy effectiveness when nominal interest rates are bounded at zero - Günter Coenen; Athanasios Orphanides; Volker Wieland (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This paper employs stochastic simulations of a small structural rational expectations model to investigate the consequences of the zero bound on nominal interest rates. We find that if the economy is subject to stochastic shocks similar in magnitude to those experienced in the U.S. over the 1980s and 1990s, the consequences of the zero bound are negligible for target inflation rates as low as 2 percent. However, the effects of the constraint are non-linear with respect to the inflation target and produce a quantitatively significant deterioration of the performance of the economy with targets between 0 and 1 percent. The variability of output increases significantly and that of inflation also rises somewhat. Also, we show that the asymmetry of the policy ineffectiveness induced by the zero bound generates a non-vertical long-run Phillips curve. Output falls increasingly short of potential with lower inflation targets.
urn:nbn:de:hebis:30-10195
Keywords: E31; E52; E58; E61; 330; Inflation targeting; price stability; monetary policy rules; liquidity trap